Characterization of Mucosal Immune Responses to Enterotoxigenic Escherichia coli Vaccine Antigens in a Human Challenge Model: Response Profiles after Primary Infection and Homologous Rechallenge with Strain H10407 - Chakraborty, Subhra; Harro, Clayton; DeNearing, Barbara; Ram, Malathi; Feller, Andrea; Cage, Alicia; Bauers, Nicole; Bourgeois, A. Louis; Walker, Richard; Sack, David A. (Clinical and vaccine immunology, 2016)
Enterotoxigenic Escherichia coli (ETEC) bacteria are the most common bacterial cause of diarrhea in children in resource-poor settings as well as in travelers. Although there are several approaches to develop an effective vaccine for ETEC, no licensed vaccines are currently available. A significant challenge to successful vaccine development is our poor understanding of the immune responses that correlate best with protection against ETEC illness. In this study, ETEC-specific mucosal immune responses were characterized and compared in subjects challenged with ETEC strain H10407 and in subjects rechallenged with the homologous organism. IgA responses to lipopolysaccharide (LPS), heat-labile toxin B subunit (LTB), and colonization factor antigen I (CFA/I) in antibody in lymphocyte supernatant (ALS), feces, lavage fluid, and saliva samples were evaluated. In all assay comparisons, ALS was the most sensitive indicator of a local immune response, but serum IgA was also a useful indirect marker of immune response to oral antigens. Volunteers challenged and then rechallenged with strain H10407 were protected from illness following rechallenge. Comparing mucosal antibody responses after primary and homologous rechallenge, protection against disease was reflected in reduced antibody responses to key ETEC antigens and in reduced fecal shedding of the H10407 challenge strain. Subjects challenged with strain H10407 mounted stronger antibody responses to LPS and LTB than subjects in the rechallenge group, while responses to CFA/I in the rechallenge group were higher than in the challenge group. We anticipate that this study will help provide an immunological benchmark for the evaluation of ETEC vaccines and immunization regimens in the future.